A Stable Antiaromatic 5, 20‐Dibenzoyl [28]Hexaphyrin(1.1.1.1.1.1): Core AuIII Metalation and Subsequent Peripheral BIII Metalation. Issue 41 (11th September 2018) - Ishida, Shin‐ichiro; Soya, Takanori; Osuka, Atsuhiro
Abstract: 5, 20‐Dibenzoyl [28]hexaphyrin(1.1.1.1.1.1) was synthesized as the first hexaphyrin bearing meso ‐aroyl substituents. The meso ‐dibenzoyl substituents are hydrogen‐bonded with the pyrrolic protons to stabilize an antiaromatic dumbbell conformer. Core metalation of this hexaphyrin with Au III afforded rectangular and aromatic [26]hexaphyrin bis‐Au III complexes, the major isomer of which was reduced with NaBH4 to give its antiaromatic 28π bis‐Au III complex. This complex allowed facile peripheral metalation with B III owing to the peripheral benzoyl substituents. Abstract : 5, 20‐Dibenzoyl [28]hexaphyrin, synthesized as a new member of meso ‐substituted hexaphyrins, is stable despite its distinct antiaromaticity. Core Au III metalation of this hexaphyrin afforded rectangular aromatic [26]hexaphyrin bis‐Au III complexes. The major isomer was reduced by NaBH4 to give the antiaromatic 28π bis‐Au III complex, the benzoyl groups of which help B III metalation, a rare example of peripheral metalation of expanded porphyrins.